CD160 and PD-1 co-expression on HIV-specific CD8 T cells defines a subset with advanced dysfunction. - Yoav Peretz; Zhong He; Yu Shi; Bader Yassine-Diab; Jean-Philippe Goulet; Rebeka Bordi; Ali Filali-Mouhim; Jean-Baptiste Loubert; Mohamed El-Far; Franck P Dupuy; Mohamed Rachid Boulassel; Cécile Tremblay; et al. (PLoS Pathogens)
Chronic viral infections lead to persistent CD8 T cell activation and functional exhaustion. Expression of programmed cell death-1 (PD-1) has been associated to CD8 T cell dysfunction in HIV infection. Herein we report that another negative regulator of T cell activation, CD160, was also upregulated on HIV-specific CD8 T lymphocytes mostly during the chronic phase of infection. CD8 T cells that expressed CD160 or PD-1 were still functional whereas co-expression of CD160 and PD-1 on CD8 T cells defined a novel subset with all the characteristics of functionally exhausted T cells. Blocking the interaction of CD160 with HVEM, its natural ligand, increased HIV-specific CD8 T cell proliferation and cytokine production. Transcriptional profiling showed that CD160(-)PD-1(+)CD8 T cells encompassed a subset of CD8(+) T cells with activated transcriptional programs, while CD160(+)PD-1(+) T cells encompassed primarily CD8(+) T cells with an exhausted phenotype. The transcriptional profile of CD160(+)PD-1(+) T cells showed the downregulation of the NFκB transcriptional node and the upregulation of several inhibitors of T cell survival and function. Overall, we show that CD160 and PD-1 expressing subsets allow differentiating between activated and exhausted CD8 T cells further reinforcing the notion that restoration of function will require multipronged approaches that target several negative regulators.